PENGEMBANGAN POJOK BACA BERBASIS KONTEKS LINGKUNGAN DALAM MENINGKATKAN LITERASI MEMBACA SEKOLAH DASAR NEGERI SE-DABIN WAHIDIN SUDIROHUSODO KECAMATAN LEBAKSIU - Susanti, Nova; Muntoha Nasukha; Tity Kusrina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an environmentally contextualized reading corner as a solution to improve reading literacy among elementary school students in Dabin Wahidin Sudirohusodo, Lebaksiu District. Initial observations indicated low reading interest and comprehension skills among students, as well as underutilized reading corners in classrooms. Using a Research and Development (R&D) approach, the development process included needs identification, design, expert validation, limited trials, and broad implementation. The results showed that reading corners designed with local environmental context and active teacher involvement significantly enhanced students' reading interest, text comprehension, and helped build a stronger culture of literacy. This program proved effective and can serve as an applicable instructional strategy that supports the School Literacy Movement (GLS) in a more targeted and contextual manner. In addition to improving cognitive skills, this literacy activity also strengthened students' social interaction through discussion and book sharing. Teachers played a strategic role in creating an engaging reading corner atmosphere and guiding structured reading activities. This research offers practical contributions to literacy development in primary education settings, particularly in areas with limited resources.